The information content in trades of inactive Nasdaq stocks - Peter Chen; Kasing Man; Chunchi Wu (The Journal of Entrepreneurial Finance and Business Ventures, 2003)
In this paper we analyze the frequency and information content of small Nasdaq stock trades and their impacts on return volatility at the intraday interval. We employ an autoregressive conditional duration (ACD) model to estimate the intensity of the arrival and information content of trades by accounting for the deterministic nature of intraday periodicity and irregular trading intervals in transaction data. We estimate and compare the price duration of thinly and heavily traded stocks to assess the differential information content of stock trades. We find that the number of transactions is negatively correlated with price duration or positively correlated with return volatility. The impact of the number of transactions on price duration or volatility is higher for thinly traded stocks. On the other hand, the persistence of the impact on price duration adjusted for intradaily periodicity is about the same for thinly and heavily traded stocks on average.
Keywords: 650